Effect of Fiber-Matrix Interface on the Mechanical Response of a Woven Carbon Fiber/Peek Composite Material - Toro-Campos, S; Toro-Campos, S (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
This work studies the relationship between the interface shear strength (IFSS) and the mechanical response of a carbon fiber-reinforced composite with a polyether-ether-ketone (PEEK) thermoplastic matrix. Two types of laminates were studied: the first kind was manufactured with as-received fiber fabrics, while specimens belonging to the second one were fabricated with thermally treated fibers where the original sizing agent was removed. IFSS values were measured with the push-in test, showing that treated fibers exhibit a 25% higher critical shear stress. Microscopic inspection of the laminates revealed that untreated specimens were prone to debonding, generating a much higher crack density. This difference was detected by the C-Scan technique and triggered in the response of both laminates under tensile tests at ±45 (Formula presented.) fiber orientation, where maximum stress and strain at break values of desized specimens showed an increase of 37% and 190%, respectively. Results confirmed that the original fiber sizing weakened the fiber-matrix interface. Lastly, the tensile response of the composite is analyzed in light of interface quality. © 2022 by the authors.